2016
DOI: 10.1038/srep26521
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profiling of small-molecule inhibitors reveals dispensability of MTH1 for cancer cell survival

Abstract: Since recent publications suggested that the survival of cancer cells depends on MTH1 to avoid incorporation of oxidized nucleotides into the cellular DNA, MTH1 has attracted attention as a potential cancer therapeutic target. In this study, we identified new purine-based MTH1 inhibitors by chemical array screening. However, although the MTH1 inhibitors identified in this study targeted cellular MTH1, they exhibited only weak cytotoxicity against cancer cells compared to recently reported first-in-class inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
108
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(121 citation statements)
references
References 44 publications
11
108
2
Order By: Relevance
“…1A), suggesting that the growth inhibition induced by TH588 is independent of oxidized stress. These results are consistent with reports that growth inhibition by TH588 may be due to off-target cytotoxic effects (17,18). However, it is possible that TH588 may act as an MTH1 inhibitor under oxidized stress conditions for cytotoxic effects.…”
Section: Combined Effects Of Th588 and Ros-inducers On The Growth Of supporting
confidence: 82%
See 3 more Smart Citations
“…1A), suggesting that the growth inhibition induced by TH588 is independent of oxidized stress. These results are consistent with reports that growth inhibition by TH588 may be due to off-target cytotoxic effects (17,18). However, it is possible that TH588 may act as an MTH1 inhibitor under oxidized stress conditions for cytotoxic effects.…”
Section: Combined Effects Of Th588 and Ros-inducers On The Growth Of supporting
confidence: 82%
“…By aiming at a redox-adaptation mechanism, MTH1 inhibition represents a new approach for a therapeutic strategy against cancer (15,16). However, recent reports have indicated that growth inhibition by MTH1 inhibitors may be due to off-target cytotoxic effects (17,18 (17). These results suggest that low concentrations of MTH1 inhibitors may suppress the enzyme activity without anti-proliferative activity.…”
Section: Introductionmentioning
confidence: 39%
See 2 more Smart Citations
“…For example, MTH1 can hydrolyze 8-oxo-rATP, 8-oxo-dATP, 8-oxo-rGTP, 8-oxo-dGTP, 2-OH-dATP and 2-OH-rATP67891011. Therefore, MTH1 can prevent the incorporation of these oxidized nucleoside triphosphates into DNA, and thus effectively reduce the mutation and cell death.…”
mentioning
confidence: 99%